The Validation of Intentions toward Assessments about Fitness of Disabled Students Scale in University Students Majoring in Adapted Physical Activity (Medico Legal Update, 2019)
The aim of the study was to identify a validation of intentions toward assessments about fitness of disabledstudents scale in university students majoring in adapted physical activity (APA). 385 participants wereselected to identify an intention toward assessment in university students majoring in APA. The use ofseries of exploratory factor analyses and confirmatory factor analyses were to determine structural validityand reliability of intentions toward assessments about fitness of disabled children scale in universitystudents specializing in APA. The outcomes of the study were adequate to validate the model fit. Further, 24questions in the questionnaire were considered as an acceptable scale and to determine the intentions towardassessments about fitness of students with disabilities in university students majoring in APA. Cronbach’sAlpha coefficients were .88, .82, .89, .80, .89, .95, and .95. Based on the results, the Intentions towardassessments about Fitness of Disabled Students (ITAFDS) scale in university students specializing in APAhad a good structural validity and reliability.